PERENCANAAN PEMBELAJARAN DI TK ST THERESIA MANGULEWA DESA RAKALABA - Maria Fransiska; Elisabeth Tantiana Ngura; Evrida Ita; Yasinta Maria Fono (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This research is motivated by the importance of mature instructional design in early childhood education to holistically stimulate students' golden age phase. The problem focuses on analyzing the learning planning process and identifying various operational obstacles faced by educators at St. Theresia Mangulewa Kindergarten, Rakalaba Village, West Golewa District, Ngada Regency. Using a qualitative approach with descriptive methods, this research's key stages were systematically implemented, including classroom activity observations, in-depth interviews with the principal and teachers, and a review of teaching materials. The data obtained were then analyzed using the Miles and Huberman interactive model, which includes data condensation techniques, narrative description presentation, and drawing conclusions. The research findings indicate that the instructional program development mechanism at this institution runs in a structured manner, encompassing the creation of semester plans, Weekly Learning Implementation Plans, Daily Learning Implementation Plans, Independent Curriculum teaching modules, and formative assessment instruments. However, its implementation is still hampered by teachers' limited time, limited literacy facilities, and a lack of training in differentiation strategies for children with special needs. The main conclusion confirms that although the efforts to adopt the new curriculum have been going well, optimizing teachers' creative competencies through ongoing workshops is urgently needed to improve the quality of education. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya rancangan instruksional yang matang di tingkat pendidikan anak usia dini guna menstimulasi fase usia emas peserta didik secara holistik. Masalah difokuskan pada analisis proses perencanaan pembelajaran serta identifikasi berbagai kendala operasional yang dihadapi oleh tenaga pendidik di TK St. Theresia Mangulewa, Desa Rakalaba, Kecamatan Golewa Barat, Kabupaten Ngada. Melalui pendekatan kualitatif dengan metode deskriptif, tahapan penting penelitian ini dilaksanakan secara sistematis meliputi pengamatan aktivitas kelas, wawancara mendalam bersama kepala sekolah dan guru, serta penelaahan dokumen perangkat ajar. Data yang diperoleh kemudian dianalisis melalui model interaktif Miles dan Huberman yang mencakup teknik kondensasi data, penyajian deskripsi naratif, hingga penarikan kesimpulan. Temuan penelitian menunjukkan bahwa mekanisme penyusunan program instruksional di lembaga ini berjalan secara terstruktur yang mencakup pembuatan rencana semester, Rencana Pelaksanaan Pembelajaran Mingguan, Rencana Pelaksanaan Pembelajaran Harian, modul ajar Kurikulum Merdeka, hingga instrumen penilaian formatif. Namun, implementasinya masih terhambat oleh keterbatasan waktu guru, minimnya fasilitas literasi, serta kurangnya pelatihan strategi diferensiasi anak berkebutuhan khusus. Simpulan utama menegaskan bahwa meskipun upaya adopsi kurikulum baru sudah berjalan baik, optimalisasi kompetensi kreatif guru melalui workshop berkelanjutan sangat mendesak dilakukan demi meningkatkan kualitas mutu pendidikan.